PENERAPAN METODE PEMBIASAAN DALAM MENANAMKAN KEDISIPLINAN ANAK USIA DINI UMUR 5-6 TAHUN - Rusiadi Rusiadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The habituation method is very effective for children aged 5-6 years. This is because children 5-6 years old have strong memories and immature personality conditions so they are easy to manage. With various habits that they do every day. That is why these habits instill moral values that are in accordance with religious and moral teachings. Therefore, after it is known that children's tendencies and instincts in teaching and habituation are very important compared to other ages, educators and parents should focus on teaching children about kindness and start getting used to it from the time they begin to understand the realities of life. Apart from that, discipline also needs to be formed from this age, because at this age the child will easily understand what we explain to the child. When discipline is taught and applied from an early age, it will help children have a good spirit of discipline that will be carried into adulthood.